53 QUANTIFICATION AND LOCALIZATION OF SRC TYROSINE KINASES IN AORTIC MYOCYTES. Issue 1 (1st January 2007) - Chen, C.; Lu, R.; Peng, S. J.; Alioua, A.; Kumar, Y.; Stefani, E.; Toro, L.
Abstract : Src tyrosine kinases are important players in cell differentiation, proliferation, and migration; however, a new signaling role in vasoconstriction has been recently discovered. Because of the possibly differing roles of the nine known Src kinases, we hypothesized that protein expression and/or localization would be distinct for each kinase. Here we sought to quantify and localize four Src tyrosine kinases, that is, c-Src, Lck, Fyn, and Yes in rat aortic myocytes. Quantitative immunoblots were done to determine protein levels in rat aortic lysates. Using recombinant Src proteins and specific antibodies, we generated standard curves from which Src family protein concentrations were intrapolated. We found c-Src to be the most abundant kinase in aorta (0.181 ± 0.02 ng/μg lysate protein, n = 3), followed by Yes (0.047 ± 0.02 ng/μg lysate protein, n = 3), whereas Lck and Fyn were practically nondetectable. Using immunocytochemistry and confocal microscopy, localization of Src family proteins was compared in freshly dissociated rat aorta myocytes and in human cultured aortic cells. c-Src localized nicely on both the cell membrane and intracellularly in rat aorta, whereas it was found mostly intracellularly in human cultured cells. Although Lck was nondetectable in our immunoblot experiments, we were able to detect it in immunocytochemistry using a higher concentration of antibody (sixfold). Lck appeared to be a membrane protein in rat aorta but resembled cytoskeletal structures in cultured cells. Lastly, Yes localized in the cytoplasm in both rat aorta and human cultures. In conclusion, the abundance and localization of c-Src in rat and human support its signaling role in vasoconstriction.